2007
DOI: 10.1016/j.neuroimage.2007.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the spinal and supraspinal pathways of dynamic mechanical allodynia in the human trigeminal system using cardiac-gated fMRI

Abstract: Following injury and inflammation, pain to light stroking (dynamic mechanical allodynia) might develop at the damaged site (primary area) or in adjacent normal tissue (secondary area).Using fMRI we mapped changes in the spinal trigeminal nucleus (spV), and supraspinal brainstem nuclei following heat/capsaicin-induced primary and secondary dynamic mechanical allodynia in the human trigeminal system. The role of these structures in dynamic mechanical allodynia has not been clarified yet in humans. During the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 53 publications
(62 reference statements)
6
42
0
Order By: Relevance
“…Furthermore, SI activity was significantly correlated with the intensity of pain that was experienced on a trial-by-trial basis in the normal state as well as during CS. These findings suggest that the increased cortical activity found in SI and ACC in previous neuroimaging studies of secondary mechanical hyperalgesia (Iadarola et al, 1998;Baron et al, 1999;Zambreanu et al, 2005;Mainero et al, 2007) mainly reflects the increased intensity of pain experienced during CS.…”
Section: Increased Pain Intensity As the Perceptual Consequence Of Cesupporting
confidence: 50%
See 1 more Smart Citation
“…Furthermore, SI activity was significantly correlated with the intensity of pain that was experienced on a trial-by-trial basis in the normal state as well as during CS. These findings suggest that the increased cortical activity found in SI and ACC in previous neuroimaging studies of secondary mechanical hyperalgesia (Iadarola et al, 1998;Baron et al, 1999;Zambreanu et al, 2005;Mainero et al, 2007) mainly reflects the increased intensity of pain experienced during CS.…”
Section: Increased Pain Intensity As the Perceptual Consequence Of Cesupporting
confidence: 50%
“…Nearly a decade of neuroimaging research has revealed that supraspinal activity is increased during mechanical hyperalgesia that is experimentally induced by capsaicin in healthy volunteers (Iadarola et al, 1998;Baron et al, 1999;Zambreanu et al, 2005;Mainero et al, 2007). Increased activity is found in the brainstem, the thalami, cerebellum, primary and secondary somatosensory cortices, insula and cingulate cortex.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge only two studies have used brain imaging techniques to define orofacial pain processing and these investigations report signal increases within SpVc during noxious cutaneous stimulation [DaSilva et al, 2002;Mainero et al, 2007]. To date, no study has examined brain activation patterns during orofacial pain which originates in deeper structures such as muscle.…”
Section: Discussionmentioning
confidence: 99%
“…After specification of the experimental design and computation of b-errors, activation projected onto the individual anatomies was displayed. Minimal cluster size was set to 3 voxel (10.7 mm 3 ) [11,36] with uncorrected P \ 0.02 (T [ 2.06) for activation in the pons and P \ 0.05 (T [ 1.65) in the medulla/spinal dorsal horn (SDH). Images were overlaid by anatomically corresponding drawings derived from two different brainstem atlases [12,15].…”
Section: Single Subject Analysismentioning
confidence: 99%